Long-Term Effects of Financial Incentives for General Practitioners on Quality Indicators in the Treatment of Patients With Diabetes Mellitus in Primary Care—A Follow-Up Analysis of a Cluster Randomized Parallel Controlled Trial - Meier, Rahel; Chmiel, Corinne; Valeri, Fabio; Muheim, Leander; Senn, Oliver; Rosemann, Thomas (Frontiers in Medicine, 2021)
Abstract Background: The effect of financial incentives on the quality of primary care is of high interest, and so is its sustainability after financial incentives are withdrawn. Objective: To assess both long-term effects and sustainability of financial incentives for general practitioners (GPs) in the treatment of patients with diabetes mellitus based on quality indicators calculated from routine data from electronic medical records. Design/Participants: Randomized controlled trial using routine data from electronic medical records of patients with diabetes mellitus of Swiss GPs. Intervention: During the study period of 24 months, all GPs received bimonthly feedback reports with information on their actual treatment as reflected in quality indicators. In the intervention group, the reports were combined with financial incentives for quality improvement. The incentive was stopped after 12 months. Measurements: Proportions of patients meeting the process quality indicator (QI) of annual HbA1c measurements and the clinical QI of blood pressure levels below 140/85 mmHg. Results: 71 GPs from 43 different practices were included along with 3,854 of their patients with diabetes mellitus. Throughout the study, the proportion of patients with annual HbA1c measurements was stable in the intervention group (78.8% to 78.9%) and decreased slightly in the control group (81.5% to 80.2%) (OR: 1.21; 95%-CI 1.04-1.42, p < 0.05). The proportion of patients achieving blood pressure levels below 140/85 mmHg decreased in the control group (51.2% to 47.2%) and increased in the intervention group (49.7% to 51.9%) (OR: 1.18; 95%-CI: 1.04-1.35, p < 0.05) where it peaked at 54.9% after 18 months and decreased steadily over the last 6 months. Conclusion: After withdrawal of financial incentives for the GPs after 12 months, some quality indicators still improved, indicating that one year might be too short to observe the full effect of such interventions. The decrease in QI achievement rates after 18 months suggests that the positive effects of time-limited financial incentives eventually wane.